1999
DOI: 10.4269/ajtmh.1999.60.173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a parasite lactate dehydrogenase-based immunochromatographic antigen detection assay (OptiMAL) with microscopy for the detection of malaria parasites in human blood samples.

Abstract: Abstract. Microscopic examination of blood smears remains the gold standard for malaria diagnosis, but is laborintensive and requires skilled operators. Rapid dipstick technology provides a potential alternative. A study was conducted in The Gambia to compare the performance of OptiMAL, an immunochromatographic antigen detection assay for the diagnosis of malaria using parasite lactate dehydrogenase, against standard microscopy in patients with suspected malaria. For initial diagnosis of Plasmodium falciparum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 4 publications
(7 reference statements)
5
42
1
Order By: Relevance
“…The reported sensitivity of ICT kits in samples with parasite density of less than 50 parasites /ml is in the range of 50-70%, while for 50-100 parasites / ml it is > 90 %. The sensitivity and specificity in the present study was higher than reported by Cook et al [11]. Palmer et al [12], found 100% specificity with sensitivity of 94% for P vivax and 88% for P falciparum.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The reported sensitivity of ICT kits in samples with parasite density of less than 50 parasites /ml is in the range of 50-70%, while for 50-100 parasites / ml it is > 90 %. The sensitivity and specificity in the present study was higher than reported by Cook et al [11]. Palmer et al [12], found 100% specificity with sensitivity of 94% for P vivax and 88% for P falciparum.…”
Section: Discussioncontrasting
confidence: 78%
“…Polymerase chain reaction based diagnosis of malaria although gives far better results is confined to few centres in India [17] . Cooke et al [11] 91.3 9 2 Gupta et al [9] 87.5 100 Palmer et al [12] 94 (P vivax) 100 88 (P falciparum) 99.9 This study 100 (P vivax) 100 96 (P falciparum) 100…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the association between false-negative RDTs and a low MOI suggests that this discrepancy may become increasingly important as malaria control becomes more effective. Based on these results, we suggest that the RDTs used to diagnose P. falciparum infection in humans should target parasite proteins thought to be essential (e.g., parasite lactic dehydrogenase) 1,[27][28][29] and should also consider proteins with identifiable (distinguishable) variants in other plasmodial species. hrp2 PCR results for smear-positive specimens with negative vs. positive HRP2-based RDT results.…”
Section: Discussionmentioning
confidence: 96%
“…1 However, alternative rapid diagnostic tests (RDTs) have been developed for use in non-endemic countries, where skilled microscopists are less available, and endemic countries for malaria control programs. A number of the most widely used RDTs are based on detection of the histidine-rich protein 2 (HRP2) product of the Plasmodium falciparum hrp2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The tests can be done in less than 15 min, require little training, and are subject to less investigator-related variation than microscopy. They are generally more than 90% sensitive and specific for falciparum malaria 57 compared with microscopy, [58][59][60][61][62] although HRP2 persistence for weeks after a malaria episode is a drawback for this test. The main limitation of these rapid tests is their cost (US$0·50-3·00), and their lower sensitivity in the diagnosis of the other human malaria infections.…”
Section: Diagnosismentioning
confidence: 99%